Atributos químicos do solo, desenvolvimento e produção de milho decorrentes do uso de diferentes condutividades elétricas da água de irrigação - Oliveira, Luciano Bestete (2011)
The impact of soil salinity on agricultural productivity is a serious problem, especially in arid and semiarid regions, which depend on irrigation to ensure an adequate supply of water for crops. In order to evaluate the soil chemical properties, development and production of corn from the use of different electrical conductivity of irrigation water, was mounted in an experiment in a completely randomized split plot with three 4 x 5 repetitions. The plots consisted of five levels of salinity of irrigation water with a conductivity of 0.1, 0.8, 1.6, 2.4 and 3.2 dS m-1 and the plots, four phenological stages corresponding vegetative growth, flowering, grain filling and physiological maturity. In each phenological phase, tests were carried out, the crop growth and soil chemical properties and the end of the experiment was determined to grain production. The application of irrigation water with different electrical conductivity reduced the dry mass of roots, shoots, leaf area, number and grain weight per plant of maize cultivar and soil PL6880 increased the availability of the calcium and sodium as well as the values of electrical conductivity of soil saturation and sodium saturation, sum of bases, cation exchange capacity and effective potential, followed by a decrease in pH value, content of aluminum and aluminum saturation. The levels of phosphorus, potassium, magnesium and potential acidity were not affected